Sistem Transportasi Terintegrasi di DKI Jakarta: Analisis Transformasi Berkeadilan Sosial - Alhamudin Maju Hamonangan Sitorus (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2022)
This study aims at analyzing the transformation process of the integrated transportation system in Jakarta City using Amartya Sen’s Capability Approach (CA) in terms of social justice. The exploration of the indicator of CA by Beyazid is used to identify social justice in the related program. Unlike previous studies that focus on the evaluation and public opinion against the integrated transportation system in Jakarta, this article fills the gap in the social justice perspective in transportation system studies. Textual Network Analysis (TNA) is used as an analysis technique. Digital approaches are used in the data collection process. This study provides the frame of the social justice principle in an integrated transportation system in Jakarta. The result shows that the developing process of the integrated transportation system already uses a social justice approach. However, the strategy of maximizing the use of mass transportation needs to be fixed.